Design, development, and testing of a cylindrical dielectric resonator antenna backed with a beehive-shaped artificial magnetic conductor for non-invasive blood glucose monitoring - Upadhyay, Nidhi; Kaur, Amanpreet; Pattanayak, Arnab; Singh, Ashima (Frontiers in Antennas and Propagation, 2025)
This article presents a novel cylindrical dielectric resonator antenna (CDRA) integrated with an artificial magnetic conductor (AMC) for non-invasive monitoring of blood glucose levels (BGL) in humans. A compact, economical, and highly sensitive RF-based sensing structure for continuous glucose monitoring that resolves the drawbacks of traditional invasive techniques was developed in this work. The suggested CDRA functions within the industrial, scientific, and medical (ISM) band (2.4–2.5 GHz) and incorporates a defective ground structure (DGS) to attain resonance at 2.4 and 2.52 GHz, offering an impedance bandwidth of 300 MHz. The antenna is small, measuring 30 mm × 30 mm × 6 mm, with an initial gain of 3.6 dBi. A beehive-shaped AMC is positioned at the back of the CDRA to improve its radiation characteristics, enhancing directivity by reducing side lobe levels and increasing the gain to 7.69 dBi. The proposed CDRA is simulated using the “Hugo” bio model (38-year-old male) available in CST MWS software. It demonstrates a specific absorption rate (SAR) of 0.036 W/kg, which is within the acceptable limits of 1.6 W/kg for human exposure. The proposed CDRA was also simulated for operation with varying glucose concentrations, and a correlation between S parameter variation and glucose variation was observed. The Debye model is used to determine the dielectric characteristics of human blood for BGL values of 80 mg/dL, 110 mg/dL, 130 mg/dL, 150 mg/dL, and 170 mg/dL. The proposed CDRA was validated for radiation parameters, and the measured values matched well with the simulated ones. The proposed CDRA shows a sensitivity of 4.5 × 10−3 dB/mg/dL. The results show that the proposed CDRA is a good candidate for measuring BGL values in humans.